Indonesian EFL teachers - Muslimin, Afif Ikhwanul; Khan, Aslam (Journal on English as a Foreign Language, 2024)
The implementation of differentiated curriculum (DC) in junior high schools has been gaining momentum in recent years as a means to address the diverse needs of students. However, more information about how English as a foreign language (EFL) teachers perceive this change is needed. This study explored English teachers' attitudes and factors that affected the introduction of DC in junior high schools. Data were collected through DC questionnaire administration and interviews using a mixed-method approach. The quantitative data were statistically analyzed using SPSS 23, while the qualitative data were thematically analyzed. The participants were the EFL teachers who actively participated in the MGMP (Musyawarah Guru Mata Pelajaran, or Subject Teacher Forum) of English Subject at the junior high school level in Batu City, East Java, Indonesia. The findings showed that all participants depicted a positive attitude toward DC implementation. However, they found some support needed from all related parties due to some challenges they met during their attempts to implement DC. This study suggests that EFL teachers' positive attitudes drive increased efforts in successfully implementing DC. However, identified challenges necessitate collaborative support from educators, administrators, and policymakers, including professional development and resource provision, for successful DC integration in EFL classrooms.